2012
DOI: 10.1029/2012gl052174
|View full text |Cite
|
Sign up to set email alerts
|

Seismic recordings of landslides caused by Typhoon Talas (2011), Japan

Abstract: Large deep‐seated landslides occurred in Nara, Wakayama, and Mie prefectures of western Japan when Typhoon Talas passed through the region on September 3–4, 2011. Signals of large landslides have been recorded by seismic networks around the world, and overall force estimates have been previously determined for large landslides using long‐period waves. This study focuses on the high‐frequency waveforms and presents signals of 18 landslides caused by Typhoon Talas (2011). The location of the landslides can be de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
102
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(108 citation statements)
references
References 15 publications
6
102
0
Order By: Relevance
“…In their studies, Surinach et al (2005) and Dammeier et al (2011) reported that rockfall spectrograms show a typical triangular shape that could be related to source effects, material entrainment during propagation and/or progressive failure and individual block impacts (Norris, 1994;McSaveney and Downes, 2002). All these characteristics can be used for event detection at different scales (Helmstetter and Garambois, 2010;Yamada et al, 2012;Kao et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their studies, Surinach et al (2005) and Dammeier et al (2011) reported that rockfall spectrograms show a typical triangular shape that could be related to source effects, material entrainment during propagation and/or progressive failure and individual block impacts (Norris, 1994;McSaveney and Downes, 2002). All these characteristics can be used for event detection at different scales (Helmstetter and Garambois, 2010;Yamada et al, 2012;Kao et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…As no clear P and S waves are visible on seismograms, conventional earthquake location techniques cannot be applied. Specific methods have been developed, based on the seismogram envelope (Yamada et al, 2012(Yamada et al, , 2013, amplitudes (Battaglia et al, 2003), wave polarization (Vilajosana et al, 2008), signal cross-correlation (Lacroix and Helmstetter, 2011) and arrival times (Hibert, 2012). Due to the emergent seismogram onset, this last technique requires advanced picking methods (e.g., Baillard et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it is known that landslides generate seismic signals, "landquakes", which contain a specific signature: low-frequency waves released by the bedrock when the mass detaches, and high-frequency waves produced by the landslide mass while it is sliding, peaking when it impacts the deposition area (e.g. Yamada et al, 2012;Chen et al, 2013). If analysed separately, they can give information on both landslide initiation and impact (Fig.…”
Section: Open Discussion: the Lesson Of A Killer Landslidementioning
confidence: 99%
“…The landslide we simulate was caused by a typhoon passing over the Kii peninsula in southwest Japan on September 4, 2011. In our simulation, we use the source location (longitude, latitude = 135.715°, 34.133°) described by YAMADA et al (2012) and the source time function derived from the waveform inversion conducted by YAMADA et al (2013). The locations of the landslide and the stations used in our simulation are presented in Fig.…”
Section: Source Model Used In Simulationsmentioning
confidence: 99%
“…1b; this map was created using topography data obtained from a 5 m mesh provided by the Geospatial Information Authority of Japan (GSI). CHIGIRA et al YAMADA et al 2012YAMADA et al , 2013. We extract the part representing the appropriate duration from their original function data and apply a cosine taper of 5 s to the beginning and end to produce a smooth function.…”
Section: Source Model Used In Simulationsmentioning
confidence: 99%